Electrode active material, electrode mixture, electrode layer, battery, and manufacturing method thereof

By employing silicon-based electrode materials with a silicon class II type crystal phase and controlled pore structure, the issue of volume change during charging and discharging is mitigated, improving battery performance and functionality.

JP7622811B1Active Publication Date: 2025-01-28TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023223258
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-01-28
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

Silicon-based electrode materials for batteries experience significant volume changes during charging and discharging, leading to a decrease in electrode function over time.

Method used

The use of silicon-based electrode materials with a specific silicon class II type crystal phase and controlled pore structure, featuring gaps within primary particles of 5 nm or less, to minimize volume changes during charging and discharging.

Benefits of technology

The controlled pore structure effectively suppresses volume changes, maintaining electrode functionality and reducing the need for excessive mechanical restraint, thereby enhancing battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622811000001_ABST
    Figure 0007622811000001_ABST
Patent Text Reader

Abstract

A primary object of the present disclosure is to provide an electrode active material that undergoes small volumetric change upon charging and discharging. [Solution] The present disclosure solves the above problem by providing an electrode active material having a silicon clathrate type II crystalline phase, which has voids inside primary particles and has a pore volume P1 of pores with a pore diameter of 5 nm or less of 0.015 cc / g or more and 0.05 cc / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode active material, an electrode mixture, an electrode layer, a battery, and methods for producing the same. [Background technology]

[0002] In recent years, the development of batteries has been actively carried out. For example, in the automobile industry, development of batteries for use in electric vehicles (BEVs), plug-in hybrid vehicles (PHEVs), or hybrid electric vehicles (HEVs) is underway. In addition, Si (silicon) is known as an electrode active material used in batteries. For example, Patent Document 1 discloses an electrode active material having a silicon clathrate II type crystal phase and having voids inside the primary particles. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-044620 A Summary of the Invention [Problem to be solved by the invention]

[0004] Silicon has a large theoretical capacity and is effective in increasing the energy density of batteries. On the other hand, silicon undergoes large volume changes during charging and discharging. Large volume changes during charging and discharging can lead to problems such as the deterioration of electrode function when the battery is repeatedly charged and discharged.

[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode active material that undergoes small volume change upon charging and discharging. [Means for solving the problem]

[0006] [1] An electrode active material having a silicon clathrate II type crystalline phase, The primary particles have voids inside. The pore volume P of pores with a pore diameter of 5 nm or less 1 is 0.015 cc / g or more and 0.05 cc / g or less.

[0007] [2] The pore volume P of pores with a pore diameter of 10 nm or less 2 The above void volume P 1 Proportion (P 1 / P 2 ) is 50% or more.

[0008] [3] The pore volume P of pores with a pore diameter of 10 nm or less 2 The electrode active material according to [1] or [2], wherein the conductivity is 0.03 cc / g or more and 0.08 cc / g or less.

[0009] [4] The pore volume P of pores with a pore diameter of 100 nm or less 3 The above void volume P 1 Proportion (P 1 / P 3 ) is 6.5% or more.

[0010] [5] The pore volume P of pores with a pore diameter of 100 nm or less 3 The electrode active material according to any one of [1] to [4], wherein the surface area of ​​the electrode active material is 0.1 cc / g or more and 0.5 cc / g or less.

[0011] [6] The electrode active material according to any one of [1] to [5], which has the silicon clathrate type II crystal phase as a main phase.

[0012] [7] An electrode mixture comprising the electrode active material according to any one of [1] to [6] and at least one of a conductive material and a binder.

[0013] [8] The electrode mixture according to [7], further comprising a solid electrolyte.

[0014] [9] The electrode mixture according to [8], wherein the solid electrolyte contained in the electrode mixture is a sulfide solid electrolyte.

[0015]

[10] An electrode layer for use in a battery, comprising: The electrode layer includes an electrode active material having a silicon clathrate II type crystal phase and having voids inside primary particles, The pore volume Q of pores with a pore diameter of 5 nm or less 1 is 0.008 cc / g or more and 0.04 cc / g or less.

[0016]

[11] The pore volume Q of pores with a pore diameter of 10 nm or less 2 The above void volume Q 1 Proportion (Q 1 / Q 2 ) is 50% or more.

[0017]

[12] The pore volume Q of pores with a pore diameter of 10 nm or less 2 The electrode layer according to

[10] or

[11] , wherein the conductivity is 0.01 cc / g or more and 0.05 cc / g or less.

[0018]

[13] The pore volume Q of pores with a pore diameter of 100 nm or less 3 The above void volume Q 1 Proportion (Q 1 / Q 3 ) is 10% or more.

[0019]

[14] The pore volume Q of pores with a pore diameter of 100 nm or less 3 The electrode layer according to any one of

[10] to

[13] , wherein the surface area of ​​the electrode layer is 0.07 cc / g or more and 0.2 cc / g or less.

[0020]

[15] A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, The battery, wherein the positive electrode layer or the negative electrode layer is the electrode layer according to any one of

[10] to

[14] .

[0021]

[16] an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; a firing step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and form a precursor active material having a silicon clathrate II type crystal phase; a liquid treatment step of treating the precursor active material with hydrofluoric acid to obtain an electrode active material; having The concentration of hydrogen fluoride in the hydrofluoric acid is 3% by weight or more, A method for producing an electrode active material, wherein the treatment time in the liquid treatment step is 3 hours or more and less than 24 hours.

[0022]

[17] In the above electrode active material, the pore volume P of pores having a pore diameter of 5 nm or less 1 The method for producing an electrode active material according to

[16] , wherein the concentration of the active material is 0.015 cc / g or more and 0.05 cc / g or less.

[0023]

[18] A preparation step of preparing an electrode active material by the method for producing an electrode active material according to

[16] or

[17] ; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; The method for producing an electrode mixture comprising the steps of:

[0024]

[19] A preparation step of preparing an electrode active material by the method for producing an electrode active material according to

[16] or

[17] ; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; The method for producing an electrode layer comprising the steps of:

[0025]

[20] A preparation step of preparing an electrode active material by the method for producing an electrode active material according to

[16] or

[17] ; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; A method for manufacturing a battery comprising the steps of: Effect of the Invention

[0026] The present disclosure has an effect of providing an electrode active material that undergoes small volumetric change upon charging and discharging. [Brief description of the drawings]

[0027] [Figure 1] FIG. 2 is a schematic perspective view illustrating a crystalline phase of Si. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 3] 1 is a flowchart illustrating a method for producing an electrode active material in the present disclosure. [Figure 4] 1 is an XRD chart of an active material before and after liquid treatment with an aqueous HF solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The electrode active material, the electrode mixture, the electrode layer, the battery, and the manufacturing methods thereof according to the present disclosure will be described in detail below.

[0029] A. Electrode active material The electrode active material of the present disclosure has a silicon clathrate II type crystal phase and has voids inside the primary particles. 1 Mostly.

[0030] According to the present disclosure, the void volume P 1 Since the amount of Li is large, the electrode active material has a small volume change due to charging and discharging. In the previous research, the inventors have found that the collapse of the voids due to the press treatment can be suppressed by increasing the void volume of the micropores having a pore diameter of 100 nm or less. Furthermore, they have found that the collapse of the voids due to the press treatment can be significantly suppressed by increasing the void volume of the micropores having a pore diameter of 10 nm or less, and at the same time, the filling rate of precipitated Li in the voids can be increased, and the volume change due to charging and discharging can be effectively suppressed.

[0031] In contrast, in the present disclosure, for example, by actively performing a liquid treatment using hydrofluoric acid, the pore volume P of minute pores having a pore diameter of 5 nm or less can be reduced. 1 It was found that it is possible to increase the amount of voids P. It is assumed that this is because, during charging, the precipitated Li fills preferentially into minute voids with a pore diameter of 5 nm or less. By actively performing the liquid treatment with hydrofluoric acid, the surface of the electrode active material is etched and the silicon clathrate I type crystal phase contained in the electrode active material disappears, and the amount of voids P 1 It is estimated that the amount of voids P 1 By increasing the volume, the volume change due to charging and discharging can be effectively suppressed.

[0032] Furthermore, the electrode active material in the present disclosure has a silicon clathrate II type crystal phase. As shown in FIG. 1(a), in the silicon clathrate II type crystal phase, a polyhedron (cage) including a pentagon or hexagon is formed by a plurality of Si elements. This polyhedron has a space inside that can contain metal ions such as Li ions. By inserting metal ions into this space, the volume change due to charging and discharging can be suppressed. In particular, in a solid-state battery, in order to suppress the volume change due to charging and discharging, it is generally necessary to apply a high confining pressure, but by using the electrode active material in the present disclosure, the confining pressure can be reduced, and as a result, the size of the confining jig can be suppressed. On the other hand, as shown in FIG. 1(b), in the diamond-type silicon crystal phase, a tetrahedron is formed by a plurality of Si elements. Since the tetrahedron does not have a space inside that can contain metal ions such as Li ions, the diamond-type silicon crystal phase is less likely to suppress the volume change due to charging and discharging than the silicon clathrate II type crystal phase.

[0033] The active material in the present disclosure is usually in the form of particles. The active material may be primary particles or secondary particles formed by agglomeration of primary particles. In either case, the primary particles usually have voids inside.

[0034] The electrode active material preferably has many pores with a pore diameter of 5 nm or less. The pore volume P of the pores with a pore diameter of 5 nm or less 1 is usually 0.015 cc / g or more, may be 0.020 cc / g or more, or may be 0.023 cc / g or more. 1 is usually 0.05 cc / g or less, may be 0.04 cc / g or less, or may be 0.035 cc / g or less. The void volume in the present disclosure means the cumulative pore volume, and can be determined, for example, by BET measurement, gas adsorption method, mercury porosimeter measurement, 3D-SEM, or 3D-TEM.

[0035] The electrode active material preferably has many pores with a pore diameter of 10 nm or less. The pore volume P of the pores with a pore diameter of 10 nm or less2 is, for example, 0.03 cc / g or more, may be 0.035 cc / g or more, or may be 0.04 cc / g or more. 2 is, for example, 0.08 cc / g or less, may be 0.07 cc / g or less, or may be 0.06 cc / g or less. 2 Void volume P 1 Proportion (P 1 / P 2 ) is, for example, 50% or more, may be 55% or more, or may be 57% or more. 1 / P 2 is, for example, 80% or less, may be 70% or less, or may be 65% or less.

[0036] The electrode active material preferably has many pores with a pore diameter of 100 nm or less. The pore volume P of the pores with a pore diameter of 100 nm or less 3 is, for example, 0.1 cc / g or more, may be 0.2 cc / g or more, or may be 0.32 cc / g or more. 3 is, for example, 0.5 cc / g or less, may be 0.45 cc / g or less, or may be 0.38 cc / g or less. 3 Void volume P 1 Proportion (P 1 / P 3 ) is, for example, 6.0% or more, may be 6.5% or more, or may be 6.9% or more. 1 / P 3 is, for example, 15% or less, may be 12% or less, or may be 10% or less.

[0037] The electrode active material preferably has voids inside the primary particles. The ratio of voids in the primary particles (porosity) is, for example, 4% or more, and may be 10% or more. The porosity is, for example, 40% or less, and may be 20% or less. The porosity can be determined, for example, by the following procedure. First, a cross section of an electrode layer containing an electrode active material is taken by ion milling. The cross section is then observed with a SEM (scanning electron microscope) to obtain a photograph of the particles. From the obtained photograph, silicon parts and void parts are clearly distinguished using image analysis software, and the image is binarized. The areas of the silicon parts and void parts are determined, and the porosity (%) is calculated from the following formula. Porosity (%) = 100 × (area of ​​void part) / ((area of ​​silicon part) + (area of ​​void part))

[0038] Average particle size of the electrode active material (D 50 ) is not particularly limited, but may be, for example, 0.1 μm or more and 50 μm or less, or 0.5 μm or more and 30 μm or less. 50 ) can be calculated, for example, from measurements using a scanning electron microscope (SEM). The BET specific surface area of ​​the electrode active material is not particularly limited, but is, for example, 30 m 2 / g or more, and 2 / g or more, 2 / g or more, 2 On the other hand, the BET specific surface area of ​​the electrode active material may be, for example, 150 m 2 / g or less.

[0039] The electrode active material has a silicon clathrate II type crystal phase. In particular, the electrode active material preferably has a silicon clathrate II type crystal phase as a main phase. The "main phase" means that the peak belonging to the crystal phase has the highest diffraction intensity among the peaks observed in X-ray diffraction measurement. The proportion of the silicon clathrate II type crystal phase contained in the electrode active material is, for example, 80% by weight or more, may be 85% by weight or more, may be 90% by weight or more, or may be 95% by weight or more. The proportion of the silicon clathrate II type crystal phase contained in the electrode active material may be 100% by weight or less than 100% by weight. The proportion of the crystal phase can be obtained by performing Rietveld analysis on the XRD measurement results and using the analysis results and the RIR method (Reference Intensity Ratio method).

[0040] The silicon clathrate II crystal phase usually belongs to the space group (Fd-3m). The silicon clathrate II crystal phase has typical peaks at 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0041] In the crystal phase of silicon clathrate type II, the peak at 2θ=20.09°±0.50° is defined as peak A, and the peak at 2θ=31.72°±0.50° is defined as peak B. The intensity of peak A is defined as I A and the intensity of peak B is I B On the other hand, the maximum intensity at 2θ = 22° to 23° is I M The range of 2θ=22° to 23° can be used as a reference because it is within the range in which no peaks of the crystal phase related to Si usually appear.

[0042] I A / I M The value of I is preferably greater than 1.A / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. A / I M The value of I is, for example, 1.75 or more, and may be 1.80 or more. A / I M The value of is, for example, 10 or less, and may be 5 or less.

[0043] I B / I M The value of I is preferably greater than 1. B / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. B / I M The value of is, for example, 1.35 or more, and may be 1.40 or more, while I B / I M The value of is, for example, 7 or less, and may be 4 or less.

[0044] The electrode active material in the present disclosure may or may not have a silicon clathrate I type crystalline phase. "Having no crystalline phase" means that no peak of the crystalline phase is confirmed in X-ray diffraction measurement. The silicon clathrate I type crystalline phase usually belongs to the space group (Pm-3n). The silicon clathrate I type crystalline phase has typical peaks at 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0045] The electrode active material in the present disclosure may or may not have a diamond-type silicon crystalline phase. In addition, the diamond-type silicon crystalline phase has typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.

[0046] When peak C at 2θ=28.44°±0.50° is observed as a peak of the diamond-type silicon crystal phase, the intensity of peak C is expressed as I C Let us assume that A / I C is, for example, greater than 1, may be 1.5 or more, may be 2 or more, or may be 3 or more. B / I C The preferred range of is I A / I C The preferred range is the same as that of the above.

[0047] The composition of the electrode active material in the present disclosure is not particularly limited, but may include Na x S 136 It is preferable that the composition is represented by (0≦x≦24). x may be 0 or may be greater than 0. On the other hand, x may be 20 or less, 10 or less, or 5 or less. The composition of the electrode active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry. In general, an unavoidable oxide film is formed on the surface of the electrode active material. Therefore, the electrode active material may contain a trace amount of O (oxygen). In addition, the electrode active material may contain a trace amount of C (carbon) derived from the manufacturing process.

[0048] The electrode active material in the present disclosure is generally used in batteries. The electrode active material in the present disclosure may be either a negative electrode active material or a positive electrode active material, with the former being preferred. Examples of the method for producing the electrode active material include the production method described in "E. Method for producing electrode active material" below.

[0049] B. Electrode composite material The electrode mixture in the present disclosure contains the above-mentioned electrode active material, and at least one of a conductive material and a binder.

[0050] According to the present disclosure, by using the above-mentioned electrode active material, an electrode mixture that undergoes small volume change upon charging and discharging is obtained.

[0051] The electrode mixture contains an electrode active material and at least one of a conductive material and a binder. The electrode active material is the same as that described in "A. Electrode Active Material" above. The electrode active material may be a negative electrode active material or a positive electrode active material, but the former is preferred. That is, the electrode mixture may be a negative electrode mixture or a positive electrode mixture, but the former is preferred.

[0052] The proportion of the electrode active material in the electrode mixture is, for example, 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. If the proportion of the electrode active material is too small, there is a possibility that sufficient energy density cannot be obtained. On the other hand, the proportion of the electrode active material is, for example, 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less. If the proportion of the electrode active material is too high, there is a possibility that the ionic conductivity and electronic conductivity of the electrode mixture are relatively reduced.

[0053] The electrode mixture contains at least one of a conductive material and a binder. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include rubber-based binders and fluoride-based binders.

[0054] The electrode mixture may further contain a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, and organic polymer electrolytes such as polymer electrolytes. Examples of the sulfide solid electrolyte include solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of the sulfide solid electrolyte include Li element, Cl element, Br element, and I element. 2 SP 2 S 5 , LiI-Li 2 SP 2 S 5 , LiI-LiBr-Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 S-GeS 2 , Li 2 SP 2 S 5 -GeS 2 The electrode mixture may further contain a dispersion medium.

[0055] C. Electrode layer The electrode layer in the present disclosure is an electrode layer for use in a battery, and includes an electrode active material having a silicon clathrate II type crystal phase and having voids inside primary particles. 1 Mostly.

[0056] According to the present disclosure, the void volume Q 1 Since the amount of the cations is large, the electrode layer exhibits small volume change upon charging and discharging.

[0057] The electrode layer preferably has many pores with a pore diameter of 5 nm or less. The pore volume Q of the pores with a pore diameter of 5 nm or less 1 is usually 0.008 cc / g or more, may be 0.010 cc / g or more, or may be 0.013 cc / g or more. 1 is usually 0.04 cc / g or less, and may be 0.03 cc / g or less.

[0058] The electrode layer preferably has many pores with a pore diameter of 10 nm or less. The pore volume Q of the pores with a pore diameter of 10 nm or less 2 is, for example, 0.01 cc / g or more, may be 0.015 cc / g or more, or may be 0.021 cc / g or more. 2 is, for example, 0.05 cc / g or less, and may be 0.04 cc / g or less. 2 Void volume Q 1 Proportion (Q 1 / Q 2 ) is, for example, 50% or more, and may be 56.9% or more. 1 / Q 2 is, for example, 90% or less, and may be 80% or less.

[0059] The electrode layer preferably has many pores with a pore diameter of 100 nm or less. The pore volume Q of the pores with a pore diameter of 100 nm or less 3 is, for example, 0.07 cc / g or more, may be 0.08 cc / g or more, or may be 0.09 cc / g or more. 3 is, for example, 0.2 cc / g or less, may be 0.15 cc / g or less, or may be 0.12 cc / g or less. 3 Void volume Q 1 Proportion (Q 1 / Q 3 ) is, for example, 10% or more, may be 12% or more, or may be 13% or more. 1 / Q 3 is, for example, 25% or less, may be 23% or less, or may be 20% or less.

[0060] The electrode layer contains an electrode active material and at least one of a conductive material and a binder. The electrode layer may also contain an electrolyte. The materials, compositions, and other matters are the same as those described in the above "A. Electrode active material" and "B. Electrode mixture". The electrode layer may be a negative electrode layer or a positive electrode layer, but the former is preferred. The thickness of the electrode layer is, for example, 0.1 μm or more and 1000 μm or less, or may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less. In addition, as a method for manufacturing the electrode layer, for example, a manufacturing method described in "F. Manufacturing method of the electrode layer" described later can be mentioned.

[0061] D.Battery Fig. 2 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 10 shown in Fig. 2 has a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the positive electrode layer 1 or the negative electrode layer 2 is the electrode layer described above in "C. Electrode layer".

[0062] According to the present disclosure, by using the above-mentioned electrode layer, a battery with small volume change due to charging and discharging is obtained. As described above, the electrode layer may be a negative electrode layer or a positive electrode layer, but the former is preferable. Hereinafter, the details of the battery in the case where the electrode layer is a negative electrode layer will be described.

[0063] 1. Negative electrode layer The negative electrode layer is a layer containing at least a negative electrode active material. The negative electrode layer is the same as that described above in "C. Electrode layer," and therefore will not be described here.

[0064] 2. Positive electrode layer The positive electrode layer is a layer containing at least a positive electrode active material, and may contain at least one of an electrolyte, a conductive material, and a binder, as necessary.

[0065] The positive electrode active material may be, for example, an oxide active material. For example, LiCoO 2 , LiMnO 2 , LiNiO 2 , LiVO 2 , LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Rock salt layered active materials such as LiMn 2 O 4 , Li 4 Ti 5 O 12 , Li(Ni 0.5 Mn 1.5 )O 4 Spinel-type active materials such as LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 Examples of the olivine type active material include those mentioned above.

[0066] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because it is possible to suppress the reaction between the oxide active material and a solid electrolyte (particularly a sulfide solid electrolyte). Examples of Li-ion conductive oxides include LiNbO 3 The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less. In addition, the positive electrode active material is, for example, Li 2 S can also be used.

[0067] The shape of the positive electrode active material may be, for example, particulate. 50 ) is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle diameter (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less.

[0068] The electrolyte used in the positive electrode layer is the same as that described in "3. Electrolyte layer". The conductive material and binder used in the positive electrode layer are the same as those described in "B. Electrode mixture" above, so the description here is omitted. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less, and may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.

[0069] 3. Electrolyte layer The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution).

[0070] The solid electrolyte is the same as that described in "B. Electrode mixture" above, so the description here is omitted. On the other hand, the electrolyte preferably contains a supporting salt and a solvent. Examples of the supporting salt (lithium salt) of the electrolyte having lithium ion conductivity include LiPF 6 , LiBF 4 , LiClO 4 , LiAsF 6 Inorganic lithium salts such as LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(FSO 2 ) 2 , LiC(CF 3 SO 2 ) 3 Examples of the solvent used in the electrolytic solution include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolytic solution preferably contains two or more kinds of solvents.

[0071] The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less, or may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.

[0072] 4.Other configurations The battery in the present disclosure preferably has a positive electrode current collector that collects the positive electrode layer and a negative electrode current collector that collects the negative electrode layer. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon.

[0073] The battery of the present disclosure may further include a restraining tool that applies a restraining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, it is preferable to apply a restraining pressure in order to form a good ion conduction path and an electron conduction path. The restraining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the restraining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less.

[0074] 5.Battery The type of battery in the present disclosure is not particularly limited, but is typically a lithium ion battery. The battery in the present disclosure may be a liquid battery in which the electrolyte layer contains an electrolytic solution, or may be a solid battery in which the electrolyte layer contains a solid electrolyte. The solid battery may be a semi-solid battery or an all-solid battery. In the present disclosure, the semi-solid battery is a battery in which the electrolyte layer has an inorganic solid electrolyte and a liquid component (e.g., an ionic liquid). In the present disclosure, the all-solid battery is a battery in which the electrolyte layer has only an inorganic solid electrolyte as an electrolyte. The battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because it can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery.

[0075] Examples of applications of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery is preferably used as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0076] E. Manufacturing method of electrode active material Fig. 3 is a flow chart illustrating a method for producing an electrode active material according to the present disclosure. In the production method shown in Fig. 3, first, a Na source and a Si source are reacted to obtain a Na-Si alloy (alloying step). Next, the Na-Si alloy is fired to reduce the amount of Na in the Na-Si alloy and form a precursor active material having a silicon clathrate II crystal phase (firing step). Next, the precursor active material is liquid-treated using hydrofluoric acid to obtain an electrode active material (liquid treatment step). In the present disclosure, the concentration of hydrofluoric acid is 3 wt% or more, and the treatment time in the liquid treatment step is 3 hours or more and less than 24 hours.

[0077] According to the present disclosure, by carrying out the liquid treatment step, it is possible to obtain an electrode active material that undergoes small volume change upon charging and discharging.

[0078] 1.Alloying process The alloying step in the present disclosure is a step of reacting a Na source and a Si source to obtain a Na-Si alloy.

[0079] The Si source is a particle containing at least Si. The Si source may be a simple substance of Si or an alloy of Si and another metal. When the Si source is an alloy, the alloy preferably contains Si as a main component. The proportion of Si in the alloy is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.

[0080] The Si source is preferably porous Si having many voids inside the primary particles. For example, a method for producing a Si source (porous Si) includes a method for producing an alloy of Li and Si (Li-Si alloy) and then removing Li from the Li-Si alloy. The Li-Si alloy is obtained, for example, by mixing Li and Si. The ratio of Li to Si (Li / Si) is, for example, 1.0 or more, may be 2.0 or more, may be 3.0 or more, or may be 4.0 or more. On the other hand, Li / Si is, for example, 8.0 or less. For example, a method for removing Li from a Li-Si alloy includes a method for reacting the Li-Si alloy with a Li extractant. For example, the Li extractant includes alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, and 1-hexanol; and acids such as acetic acid, formic acid, propionic acid, and oxalic acid.

[0081] Also, as a method for producing a Si source (porous Si), for example, there is a method in which an alloy of Mg and Si (Mg-Si alloy) is produced, and then Mg is removed from the Mg-Si alloy. The Mg-Si alloy can be obtained, for example, by heating a mixture of Mg and Si. The ratio of Mg to Si (Mg / Si) is, for example, 1.0 or more, may be 1.5 or more, or may be 2.0 or more. On the other hand, Mg / Si is, for example, 6.0 or less. As a method for removing Mg from an Mg-Si alloy, for example, there is a method in which Mg in the Mg-Si alloy is changed to MgO by heating the Mg-Si alloy in an inert gas atmosphere containing oxygen, and then MgO is removed with an acid solution. As an acid solution, for example, there is an aqueous solution containing hydrochloric acid (HCl) and hydrogen fluoride (HF).

[0082] In addition, examples of methods for producing a Si source (porous Si) include a method of producing an alloy of Mg and Si (Mg-Si alloy), then removing Mg from the Mg-Si alloy, then producing an alloy of Si and Li (Li-Si alloy) from which the Mg has been removed, and then removing Li from the Li-Si alloy.

[0083] On the other hand, the Na source contains at least Na. Examples of the Na source include metallic Na, NaH, and a metallic Na dispersion in which metallic Na particles are dispersed in oil.

[0084] As a method for obtaining a Na-Si alloy by reacting a Na source and a Si source, for example, a method of heating a mixture containing a Na source and a Si source can be mentioned. The heating temperature is, for example, 300°C or more, may be 310°C or more, may be 320°C or more, or may be 340°C or more. On the other hand, the heating temperature is, for example, 800°C or less, may be 600°C or less, or may be 450°C or less. In addition, the alloying step is preferably performed under an inert atmosphere such as an Ar atmosphere.

[0085] The Na-Si alloy preferably has a Zintl phase. The Zintl phase has typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14° in an X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, or within a range of ±0.30°. The Na-Si alloy preferably has a Zintl phase as a main phase.

[0086] The composition of the Na-Si alloy is not particularly limited, but may be any of the following: z S 136 It is preferable that the composition is represented by (121≦z≦151). z may be 126 or more, or 131 or more. On the other hand, z may be 141 or less. The Na-Si alloy may contain elements other than Na and Si. Examples of the other elements include Li, K, Rb, Cs, Ba, Ga, and Ge.

[0087] 2. Firing process The firing step in the present disclosure is a step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and form a precursor active material having a silicon clathrate II type crystal phase.

[0088] The firing conditions of the Na-Si alloy are appropriately adjusted so as to obtain a desired precursor active material. The firing temperature is, for example, 300°C or higher and 400°C or lower. Meanwhile, the firing time is, for example, 5 hours or higher and 120 hours or lower. The firing process may be performed in a reduced pressure atmosphere or in a normal pressure atmosphere.

[0089] In the firing step, it is preferable to use a scavenger that captures Na in the Na-Si alloy. One example of the scavenger is a Na getter agent that reacts with Na vapor generated from the Na-Si alloy. The Na getter agent is disposed, for example, in a state where it is not in contact with the Na-Si alloy. Examples of the Na getter agent include SiO, MoO 3 , FeO, Fe 3 O 4 When a Na getter agent is used, the firing step is preferably carried out in a reduced pressure atmosphere.

[0090] Another example of the scavenger is a Na trapping agent that directly reacts with the Na-Si alloy to receive Na. The Na trapping agent is, for example, placed in contact with the Na-Si alloy. The Na trapping agent is, for example, CaCl 2 , AlF 3 , CaBr 2 , CaI 2 , Fe 3 O 4 , FeO, MgCl 2 , ZnO, ZnCl 2 , MnCl 2 When a sodium trapping agent is used, the firing step may be carried out in a reduced pressure atmosphere or in a normal pressure atmosphere.

[0091] 3. Liquid treatment process The liquid treatment step in the present disclosure is a step of liquid treating the precursor active material with hydrofluoric acid to obtain an electrode active material. Hydrofluoric acid is an aqueous solution in which hydrogen fluoride (HF) is dissolved in water.

[0092] The concentration of hydrogen fluoride in hydrofluoric acid is usually 3% by weight or more, may be 4% by weight or more, or may be 5% by weight or more. Meanwhile, the concentration of hydrogen fluoride in hydrofluoric acid is, for example, 10% by weight or less. Furthermore, the treatment time of the liquid treatment is usually 3 hours or more, may be 4 hours or more, or may be 5 hours or more. Meanwhile, the treatment time of the liquid treatment is usually less than 24 hours, may be 15 hours or less, or may be 10 hours or less. The temperature of the liquid treatment is not particularly limited, but is, for example, room temperature.

[0093] Examples of the method for treating the precursor active material with hydrofluoric acid include a method of immersing the precursor active material in hydrofluoric acid and a method of applying hydrofluoric acid to the precursor active material.

[0094] 4. Electrode active material The electrode active material obtained by each of the above-mentioned steps has a silicon clathrate II type crystal phase. The electrode active material also has a pore volume P 1 is preferably 0.015 cc / g or more and 0.05 cc / g or less. Preferred aspects of the electrode active material are the same as those described above in "A. Electrode active material."

[0095] F. Manufacturing method of electrode mixture The present disclosure provides a method for producing an electrode mixture, the method including: a preparation step of preparing an electrode active material by the above-mentioned method for producing an electrode active material; and a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture.

[0096] According to the present disclosure, by using the above-mentioned electrode active material, it is possible to obtain an electrode mixture that has a small volume change due to charging and discharging. The preparation process is the same as that described in "E. Manufacturing method of electrode active material" above.

[0097] The electrode mixture usually contains an electrode active material and at least one of a conductive material and a binder. The conductive material and the binder are the same as those described in "B. Electrode mixture" above. The electrode mixture may or may not further contain a dispersion medium. The electrode mixture is usually obtained by mixing the electrode active material with at least one of a conductive material and a binder. The mixing method is not particularly limited, and a known method can be adopted. The preferred embodiment of the obtained electrode mixture is the same as that described in "B. Electrode mixture" above.

[0098] G. Method of manufacturing the electrode layer The present disclosure provides a method for producing an electrode layer, comprising: a preparation step of preparing an electrode active material by the above-mentioned method for producing an electrode active material; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; and an electrode layer formation step of forming an electrode layer using the electrode mixture.

[0099] According to the present disclosure, by using the above-mentioned electrode active material, it is possible to obtain an electrode layer with small volume change due to charging and discharging. The preparation process and the mixing process are the same as those described in the above "E. Manufacturing method of electrode active material" and "F. Manufacturing method of electrode mixture".

[0100] The electrode layer forming step is a step of forming an electrode layer using the electrode mixture. The method of forming the electrode layer is not particularly limited, and a known method can be adopted. For example, a method of coating the electrode mixture on an electrode current collector can be used as a method of forming the electrode layer. When forming the electrode layer, a pressing process may be performed to press the electrode layer in the thickness direction. Examples of the pressing process include a roller press and a flat plate press. In addition, when the electrode mixture is a slurry containing a dispersion medium, it is preferable to dry the electrode current collector after coating it.

[0101] The electrode layer forming step may be a positive electrode layer forming step of forming a positive electrode layer, or may be a negative electrode layer forming step of forming a negative electrode layer.

[0102] H. Battery manufacturing method The present disclosure provides a battery manufacturing method, including: a preparation step of preparing an electrode active material by the above-mentioned electrode active material manufacturing method; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; and an electrode layer formation step of forming an electrode layer using the electrode mixture.

[0103] According to the present disclosure, by using the above-mentioned electrode active material, a battery with small volume change due to charging and discharging can be obtained. The preparation step, mixing step, and electrode layer forming step are the same as those described in the above "E. Manufacturing method of electrode active material", "F. Manufacturing method of electrode composite material", and "G. Manufacturing method of electrode layer". The manufacturing method of a battery in the present disclosure may further include other steps such as an electrolyte layer forming step for forming an electrolyte layer. In addition, the preferred embodiment of the obtained battery is the same as that described in the above "D. Battery".

[0104] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0105] [Comparative Example 1] Metallic Li and Si powder were weighed out in a molar ratio of 4:1, and reacted in a mortar under Ar atmosphere at room temperature for 0.5 hours. 4 Si was obtained. The Li obtained 4 Si was reacted with ethanol under an Ar atmosphere. The resulting reaction products were Si and CH 3 CH 2 The reaction product was filtered, and the solid matter was dried at 120°C for 3 hours or more to obtain powdered porous Si.

[0106] The obtained porous Si was used and NaH was used as a Na source to produce a Na-Si alloy. The NaH used was washed with hexane in advance. NaH and porous Si were weighed out to a molar ratio of 1.05:1, and mixed using a cutter mill. The mixture of NaH and porous Si was heated in a heating furnace under an Ar atmosphere at 475°C for 40 hours to obtain a powdered Na-Si alloy.

[0107] The obtained Na-Si alloy was used and further treated with AlF as a Na trapping agent. 3 The silicon clathrate was produced by the solid-phase method using Na-Si alloy and AlF 3 The powdered reaction raw material was placed in a stainless steel reaction vessel and heated in an Ar atmosphere at 310°C for 60 hours in a heating furnace to react with the raw material, and a precursor active material was obtained.

[0108] The obtained precursor active material is believed to contain NaF and Al as by-products. 3 and H 2 The mixture was washed with a mixed solvent of 10:90 by volume of HF and 10:10. This removed by-products from the reaction product. After washing, the mixture was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain a powder. 5 g of the obtained powder was then weighed out and treated with a 3% by weight aqueous HF solution for 1 hour. After the treatment, the mixture was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain an electrode active material.

[0109] [Comparative Example 2] An electrode active material was obtained in the same manner as in Comparative Example 1, except that when preparing powdered porous Si, metallic Li and Si powder were used in a molar ratio of 4.75:1, and when preparing powdered Na-Si alloy, heating was performed in a heating furnace under an Ar atmosphere at 400°C for 40 hours.

[0110] [Example 1] An electrode active material was obtained in the same manner as in Comparative Example 1, except that when preparing powdered porous Si, metallic Li and Si powder were used in a molar ratio of 4.75:1, and the treatment time in the liquid treatment with the HF aqueous solution was changed to 3 hours.

[0111] [Example 2] An electrode active material was obtained in the same manner as in Comparative Example 1, except that when preparing powdered porous Si, metallic Li and Si powder were used in a molar ratio of 4.75:1, and when performing liquid treatment with an HF aqueous solution, the treatment time was changed to 5 hours.

[0112] [Example 3] An electrode active material was obtained in the same manner as in Comparative Example 1, except that the treatment time in the liquid treatment with the HF aqueous solution was changed to 5 hours.

[0113] [Comparative Example 3] An electrode active material was obtained in the same manner as in Comparative Example 1, except that when preparing powdered porous Si, metallic Li and Si powder were used in a molar ratio of 4.75:1, and when performing liquid treatment with an HF aqueous solution, the concentration was changed to 1 wt %, and the treatment time was changed to 5 hours.

[0114] [Comparative Example 4] An electrode active material was obtained in the same manner as in Comparative Example 1, except that when preparing powdered porous Si, metallic Li and Si powder were used in a molar ratio of 4.75:1, and when performing liquid treatment with an HF aqueous solution, the treatment time was changed to 24 hours.

[0115] [Comparative Example 5] Crystalline Si (SIEPB23, manufactured by Kojundo Kagaku Co., Ltd.) was prepared and pulverized by mechanical milling. Specifically, 1 g of crystalline Si and 53 g of zirconia balls with a diameter of 1 mm were placed in a container and sealed, and mechanical milling was performed at 200 rpm for 3 hours using a planetary ball mill (manufactured by Fritsch Co., Ltd.). Thereafter, a liquid treatment was performed for 5 hours using an aqueous HF solution with a concentration of 3% by weight. After the liquid treatment, the mixture was filtered, and the filtered solid matter was dried at 120°C for 3 hours or more to obtain an electrode active material. The liquid treatment conditions for the electrode active materials in Examples 1 to 3 and Comparative Examples 1 to 5 are shown in Table 1.

[0116] [Table 1]

[0117] [evaluation] (XRD measurement) X-ray diffraction (XRD) measurement using CuKα radiation was performed on the electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4. As a result, it was confirmed that all of the electrode active materials had a silicon clathrate II type crystal phase as the main phase.

[0118] The intensity of peak A located near 2θ=20.09° in the silicon clathrate II crystal phase is I A The intensity of peak B located near 2θ = 31.72° is I B The maximum intensity at 2θ = 22° to 23° was defined as I M And, I A / I M and I B / I M As a result, the electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 all had a I A / I M is greater than 1 and I B / I M was also greater than 1.

[0119] In addition, in Examples 1 to 3 and Comparative Examples 1 to 4, the proportion of the silicon clathrate I type crystal phase before the liquid treatment with the HF aqueous solution was determined by the RIR method (Reference Intensity Ratio method). The results are shown in Table 1. As shown in Table 1, it was confirmed that the precursor active material contained a silicon clathrate I type crystal phase before the liquid treatment with the HF aqueous solution. In addition, as shown in FIG. 4, it was confirmed that the silicon clathrate I type crystal phase disappeared before and after the liquid treatment with the HF aqueous solution.

[0120] (Measurement of void volume) The pore volume of the electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was determined. Specifically, a high-precision gas adsorption amount measuring device (BELSORP MAXII, manufactured by Microtrac Bel) was used to measure the pore volume P 1 , the amount of voids P with a pore diameter of 10 nm or less 2 , the amount of voids P with a pore diameter of 100 nm or less 3 The results are shown in Table 2.

[0121] (Specific surface area measurement) A specific surface area measuring device was used to determine the BET specific surface area of ​​the electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5. The results are shown in Table 2.

[0122] [Table 2]

[0123] As shown in Table 2, the electrode active materials obtained in Examples 1 to 3 have a smaller void volume P 1 It was confirmed that the silicon clathrate I crystal phase is more easily dissolved in an HF aqueous solution than the silicon clathrate II crystal phase, so the silicon clathrate I crystal phase disappears by the liquid treatment with an HF aqueous solution, and the amount of voids P 1 It is estimated that the number of cases has increased.

[0124] (Production of all-solid-state batteries) The electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 and 2 were used as negative electrode active materials to fabricate all-solid-state batteries, respectively. The fabrication method was as follows.

[0125] (1) Preparation of the negative electrode The obtained electrode active material and sulfide solid electrolyte (Li 2 SP 2 S 5 A butyl butyrate solution containing 5% by weight of PVDF-based binder, butyl butyrate, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a negative electrode current collector (Cu foil, manufactured by UACJ) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C. This resulted in a negative electrode having a negative electrode current collector and a negative electrode layer.

[0126] (2) Preparation of the positive electrode The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , average particle size 6 μm), sulfide solid electrolyte (Li 2 SP 2 S 5 A butyl butyrate solution containing 5% by weight of PVDF-based binder, butyl butyrate, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with an ultrasonic dispersion device, and shaken for 3 minutes with a shaker. The mixture was applied to a positive electrode collector (Al foil, manufactured by Showa Denko) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100 ° C. This resulted in a positive electrode having a positive electrode collector and a positive electrode layer. The area of ​​the positive electrode was smaller than that of the negative electrode.

[0127] (3) Preparation of solid electrolyte layer A polypropylene container is filled with a sulfide solid electrolyte (Li 2 SP 2 S 5 A heptane solution containing 5% by weight of a butylene rubber-based binder, a 5% by weight tungsten-based glass ceramic, and heptane were added, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied onto a release sheet (Al foil) by the blade method using an applicator, and dried on a hot plate at 100°C for 30 minutes. This resulted in a transfer member having a release sheet and a solid electrolyte layer.

[0128] (4) Fabrication of all-solid-state batteries A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the resultant was set in a roll press machine and pressed at 100 kN / cm and 165° C. This produced a first laminate.

[0129] Next, the negative electrode was set in a roll press machine and pressed at 60 kN / cm and 25°C. This resulted in a pressed negative electrode. Then, a solid electrolyte layer for bonding and a transfer member were arranged in order from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer on the transfer member were arranged so as to face each other. The obtained laminate was set in a planar uniaxial press machine and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. This resulted in a second laminate.

[0130] Next, the solid electrolyte layer for bonding in the first laminate and the solid electrolyte layer in the second laminate were arranged to face each other, and then set in a flat uniaxial press and pressed at 200 MPa and 120° C. for 1 minute to obtain an all-solid-state battery.

[0131] (5) Measurement of void volume and volume expansion rate The void volume of the pressed negative electrode was determined. Specifically, a high-precision gas adsorption amount measuring device (BELSORP MAXII, manufactured by Microtrac Bel) was used to measure the void volume Q 1 , the amount of voids Q with a pore diameter of 10 nm or less 2 , the amount of voids Q with a pore diameter of 100 nm or less 3 The results are shown in Table 3. The obtained all-solid-state battery was charged and the volume expansion rate was measured. The test conditions were a confining pressure (constant size) of 5 MPa, charging at 0.1 C, and a cut voltage of 4.55 V. The confining pressure at 4.55 V was measured, and the increase in the confining pressure from the state before charging was determined, and the volume expansion rate was calculated. The results are shown in Table 3. The results of the volume expansion rate in Table 3 are relative values ​​when the result of Comparative Example 1 is taken as 100. The change in the amount of voids due to pressing is shown in Table 4.

[0132] [Table 3]

[0133] [Table 4]

[0134] As shown in Table 3, the electrode active materials obtained in Examples 1 to 3 have a larger pore volume Q of pores having a pore diameter of 5 nm or less than that of the electrode active materials obtained in Comparative Examples 1 and 2. 1 As shown in Table 4, Q 1 / P 1 Q 2 / P 2 It was confirmed that larger voids with a pore diameter of 5 nm or less were difficult to be crushed by pressing. Also, as shown in Table 3, it was confirmed that Examples 1 to 3 were able to reduce the volume expansion coefficient compared to Comparative Examples 1 and 2. In particular, Examples 2 and 3 were able to reduce the volume expansion coefficient significantly compared to Comparative Example 1. [Explanation of symbols]

[0135] 1 ... Positive electrode layer 2 ... Negative electrode layer 3 … Electrolyte layer 4 … Positive current collector 5 … Negative current collector 10 … Battery

Claims

1. An electrode active material having a silicon clathrate II type crystalline phase, The primary particles have voids inside. The pore volume P of pores with a pore diameter of 5 nm or less 1 is 0.015 cc / g or more and 0.05 cc / g or less.

2. The pore volume P of pores having a pore diameter of 10 nm or less 2 The void volume P 1 The ratio (P 1 / P 2 2. The electrode active material according to claim 1, wherein the ratio of the surface area to the surface area of ​​the electrode active material is 50% or more.

3. The pore volume P of pores having a pore diameter of 10 nm or less 2 The electrode active material according to claim 1 , wherein the surface area is 0.03 cc / g or more and 0.08 cc / g or less.

4. The pore volume P of pores having a pore diameter of 100 nm or less 3 The amount of void P 1 The ratio (P 1 / P 3 2. The electrode active material according to claim 1, wherein the content of ZnO in the electrolyte is 6.5% or more.

5. The pore volume P of pores having a pore diameter of 100 nm or less 3 The electrode active material according to claim 1 , wherein the surface area is 0.1 cc / g or more and 0.5 cc / g or less.

6. The electrode active material according to claim 1 , which has the silicon clathrate II type crystal phase as a main phase.

7. An electrode mixture comprising the electrode active material according to any one of claims 1 to 6 and at least one of a conductive material and a binder.

8. The electrode mixture of claim 7 , further comprising a solid electrolyte.

9. The electrode mixture according to claim 8 , wherein the solid electrolyte contained in the electrode mixture is a sulfide solid electrolyte.

10. An electrode layer for use in a battery, comprising: the electrode layer includes an electrode active material having a silicon clathrate II type crystal phase and having voids inside primary particles, The pore volume Q of the pores having a pore diameter of 5 nm or less in the electrode active material 1 is 0.008 cc / g or more and 0.04 cc / g or less.

11. The pore volume Q of the pores in the electrode active material having a pore diameter of 10 nm or less 2 The void volume Q 1 The proportion of (Q 1 / Q 2 11. The electrode layer according to claim 10, wherein the ratio of the surface area to the surface area is 50% or more.

12. The pore volume Q of the pores in the electrode active material having a pore diameter of 10 nm or less. 2 The electrode layer according to claim 10 , wherein the surface area is 0.01 cc / g or more and 0.05 cc / g or less.

13. The pore volume Q of the pores in the electrode active material having a pore diameter of 100 nm or less. 3 The void volume Q 1 The proportion of (Q 1 / Q 3 11. The electrode layer according to claim 10, wherein the ratio of the surface area to the surface area is 10% or more.

14. The pore volume Q of the pores in the electrode active material having a pore diameter of 100 nm or less. 3 The electrode layer according to claim 10 , wherein the surface area is 0.07 cc / g or more and 0.2 cc / g or less.

15. A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery, wherein the positive electrode layer or the negative electrode layer is an electrode layer according to any one of claims 10 to 14.

16. an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; a firing step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and form a precursor active material having a silicon clathrate II type crystalline phase; a liquid treatment step of treating the precursor active material with hydrofluoric acid to obtain an electrode active material; having The concentration of hydrogen fluoride in the hydrofluoric acid is 3% by weight or more and 5% by weight or less, The method for producing an electrode active material, wherein the treatment time in the liquid treatment step is 3 hours or more and less than 24 hours.

17. An alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; a firing step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and form a precursor active material having a silicon clathrate II type crystalline phase; a liquid treatment step of treating the precursor active material with hydrofluoric acid to obtain an electrode active material; having The concentration of hydrogen fluoride in the hydrofluoric acid is 3% by weight or more, In the electrode active material, the pore volume P of pores having a pore diameter of 5 nm or less 1 is 0.015 cc / g or more and 0.05 cc / g or less.

18. A preparation step of preparing an electrode active material by the method for producing an electrode active material according to claim 16 or 17; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; The method for producing an electrode mixture comprising the steps of:

19. A preparation step of preparing an electrode active material by the method for producing an electrode active material according to claim 16 or 17; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; The method for producing an electrode layer comprising the steps of:

20. A preparation step of preparing an electrode active material by the method for producing an electrode active material according to claim 16 or 17; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; A method for manufacturing a battery comprising the steps of:

Citation Information

Patent Citations

  • Active material, negative electrode layer, battery and these manufacturing methods

    JP2021158003A

  • Method for manufacturing negative electrode active material

    JP2023043948A

  • Active material, negative electrode layer, battery, and manufacturing method thereof

    JP2023044620A

  • Active material, negative electrode layer, battery, and method of manufacturing them

    JP2023167083A